New insights into the Western Iberian Buoyant Plume: Interaction between the Douro and Minho River plumes under winter conditions. (February 2016) - Mendes, Renato; Sousa, Magda Catarina; deCastro, Maite; Gómez-Gesteira, Moncho; Dias, João Miguel
Highlights: Interaction between two coastal river plumes demonstrated by numerical modeling. Important role of Douro inflow on the northward WIBP current stabilization. Douro plume impacts Minho plume modifying the freshwater fate. Upstream plume prevents offshore freshwater exportation by small-scale eddies. Reduced stratification induced by Douro plume enhances water exchange with Rias Baixas. Abstract: The Douro and Minho Rivers are the most important freshwater contributors on the northwestern coast of the Iberian Peninsula. Although their interaction is poorly understood, it is well known that they generate the Western Iberian Buoyant Plume (WIBP). This study aims to research the interaction of the Douro and Minho estuarine plumes under winter conditions, with a focus on the changes induced in normal WIBP patterns. Additionally, it will assess the impact of these changes on the Rias Baixas dynamics. An integrated analysis of the dispersion of these plumes was performed through hydrodynamic and Lagrangian numerical simulations of representative winter conditions for January and February 2010. Several simulations were carried out to study the interaction between plumes and their direct and indirect influence on coastal circulation. Under downwelling-favorable winds, the interaction between the Douro and Minho plumes is clear. Both plumes tend to be confined against the coast, as Ekman transport generates a buoyant coastal band with high surface currents. Douro estuary inflow reaches the Minho River coastal region and interacts with the Minho plume to modify freshwater fate. The Douro estuarine plume plays an important role in stabilizing WIBP, by preventing small-scale eddy generation and, consequently, the offshore freshwater transport. In addition, the Douro River has been shown to have a crucial influence on plume stratification, by enhancing the water exchange with the Rias de Vigo and Pontevedra. Interaction between the Douro and Minho plumes is unlikely during upwelling events. Finally, despite the Douro River having the higher discharge, it has a small direct influence on the Rias Baixas.